2021
DOI: 10.5114/aoms.2018.73333
|View full text |Cite
|
Sign up to set email alerts
|

Plasma renin activity, serum aldosterone concentration and selected organ damage indices in essential arterial hypertension

Abstract: Introduction The aim of this study was to assess the relations between plasma renin activity (PRA), serum aldosterone concentration (ALDO) and selected asymptomatic organ damage (AOD) indices in mild primary arterial hypertension (AH). Material and methods We measured PRA, ALDO, and selected AOD indices (carotid-femoral pulse wave velocity (cfPWV), central aortic pulse pressure (cPP), estimated glomerular filtration rate (eGFR)) in 122 patients with untreated AH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…Several studies reported an association between PRA and kidney diseases in population of cardiovascular diseases with inconsistent results 12–14,24 . Our study suggests PRA as an independent predictor for future incident kidney damage, mainly for positive proteinuria, in hypertensive diabetic patients, who have higher risk for development of kidney disease.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Several studies reported an association between PRA and kidney diseases in population of cardiovascular diseases with inconsistent results 12–14,24 . Our study suggests PRA as an independent predictor for future incident kidney damage, mainly for positive proteinuria, in hypertensive diabetic patients, who have higher risk for development of kidney disease.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies reported an association between PRA and kidney diseases in population of cardiovascular diseases with inconsistent results. 12 , 13 , 14 , 24 Our study suggests PRA as an independent predictor for future incident kidney damage, mainly for positive proteinuria, in hypertensive diabetic patients, who have higher risk for development of kidney disease. The results are compatible with interventional studies that aliskiren showed renoprotection by decreasing proteinuria or albuminuria, whereas had no effects for serum creatinine or eGFR.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Jalur fisiologis RAAS bersifat esensial dalam menjaga kondisi normotensi, vasokonstriksi, serta retensi volume darah. 2,5 Selama ini, aldosterone-to-renin ratio (ARR) dipercaya sebagai parameter pemeriksaan screening yang kuat dibandingkan pengukuran kadar aldosterone untuk kondisi primary aldosteronism (PA). ARR dapat menjadi indeks aktivitas aldosterone serta peningkatan sensitivitas terhadap garam.…”
Section: Medical Reviewunclassified